2016
DOI: 10.3233/jad-160007
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fibrillar Oligomeric Amyloid-β within Synapses

Abstract: Alzheimer's disease (AD) is characterized by memory loss, insidious cognitive decline, profound neurodegeneration, and the extracellular accumulation of amyloid-β (Aβ) peptide in senile plaques and intracellular accumulation of tau in neurofibrillary tangles. Loss and dysfunction of synapses are believed to underlie the devastating cognitive decline in AD. A large amount of evidence suggests that oligomeric forms of Aβ associated with senile plaques are toxic to synapses, but the precise sub-synaptic localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 46 publications
10
77
0
1
Order By: Relevance
“…Moreover, the extent of Aβ binding to synapses was similar in two different sources of 331 wild type mice ( Figure 5B and C), and the pattern observed was reminiscent of that 332 seen in AD brain (Pickett et al, 2016). 333 There is evidence that APP can act as a receptor for Aβ (Melchor and Van Nostrand,334 2000; Van Nostrand et al, 2002;Yankner and Lu, 2009;Fogel et al, 2014;Kirouac et 335 al., 2017) and that APP may mediate increased -excitatory drive (Fogel et al, 2014).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the extent of Aβ binding to synapses was similar in two different sources of 331 wild type mice ( Figure 5B and C), and the pattern observed was reminiscent of that 332 seen in AD brain (Pickett et al, 2016). 333 There is evidence that APP can act as a receptor for Aβ (Melchor and Van Nostrand,334 2000; Van Nostrand et al, 2002;Yankner and Lu, 2009;Fogel et al, 2014;Kirouac et 335 al., 2017) and that APP may mediate increased -excitatory drive (Fogel et al, 2014).…”
mentioning
confidence: 73%
“…electrophysiology recordings certain brain slices from wild-type and 567 APP knock mice(Figs 3 and 4) were processed for array tomography(Koffie et al, 568 2009;Pickett et al, 2016). Slices were fixed in PBS containing 4% paraformaldehyde 569 and 2.5% sucrose at 4°C overnight.…”
mentioning
confidence: 99%
“…Previous immunohistochemistry studies have confirmed that many synaptic proteins can be found dispersed throughout plaques[32, 65], therefore, this may be the case in rpAD plaques also. Aβ oligomers are known to accumulate in synapses, particularly in synapses near plaques[60]. Aβ oligomers are also known to be toxic to synapses[25], and the presence of synaptic Aβ oligomers correlates with cognitive impairment in early AD[8].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, soluble oligomeric forms of A have gained importance in AD research owing to their heightened cytotoxicity and effects on synaptic functions (106)(107)(108)(109)(110). Several studies have directly linked acute exposure to Aβ to loss of functions such as neuronal oscillations in various brain regions (108,109,(111)(112)(113)(114). An inquiry into this misfolded protein's potential role in network dysfunctions will greatly aid the design of therapeutic interventions aimed at preventing and/or rescuing neuronal dysfunction.…”
Section: Alzheimer's Disease and Network Dysfunctionmentioning
confidence: 99%